Maximum likelihood estimation of ruin probability in the classical risk model with exponential claims - Pantí-Trejo, Henry G. (2022)
Maximum likelihood estimators are calculated for the parameters that define the compound Poisson process in the classical risk process with exponential claims. It is proved consistency and asymptotic normality for estimators obtained. Finally, with the help of invariance property of the maximum likelihood estimators, asymptotic normality and delta method, point and interval estimation of the ruin probability is performed.